Pemanfaatan Sistem Informasi Geografis (SIG) Untuk Pemantauan Kerusakan Lahan di Kota Tanjungpinang, Kepulauan Riau - Danardono Danardono (Cakrawala Repositori IMWI, 2023)
Land management, especially soil that is not in accordance with the rules, can cause damage / change in soil properties which ultimately impacts on the disruption of biomass production. The lack of existing data on land and or soil damage, especially in Tanjungpinang City, leads to less than optimal supervision and control of land management. Mapping the condition of land damage is absolutely necessary to be able to control land management. The purpose of the research is to assess land degradation in Tanjungpinang City, Riau Islands for biomass production. Land degradation can be modeled by scoring and overlaying four parameters: land use, slope, soil type, and rainfall, resulting in a map of potential land degradation. The results show that the criteria for land degradation in Tanjungpinang City are lightly degraded and moderately degraded. Moderately degraded criteria have the largest area spread across Dompak, Batu Sembilan, Melayu Kota Piring, Bukit Cermin, Tanjungpinang Barat, Tanjungpinang Timur, Kampung Baru, and Tanjung Ayun Sakti urban villages. The main limiting factors that restrict land use in Tanjungpinang City are soil type and slope.